Epidemio-clinical study of the first iterative cesarean in the gynecology-obstetric service at the teaching hospital of Cocody - Adjoby, Cassou R.; Koffi, Soh V.; Balde, Ibrahima S.; Effoh, Denis; Lagaud, Eleonore Gbary; Angoi, Aya V.; Mamy, Nawa M.; Soro, Ngolo A.; Soumahoro, Zingbe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The iterative caesarean section, is a caesarean section that is performed on a uterus already healed, therefore for fear of maternal and perinatal risks, is recognized as one of the main causes of the inflation of caesarean section in the world. One in three caesarean sections is performed because of a scar uterus. Objective of this study was to analyse the epidemiological and clinical factors of iterative caesarean sections in the gynecology-obstetrics department at the Teaching Hospital of Cocody (Abidjan). Methods: This was a retrospective and descriptive study conducted from June 1st, 2018 to May 31st, 2019, including 349 iterative caesarean section cases. Results: The first iterative C-section accounted for 16.1% of the C-section indications during the study period. The average age of the patients was 30 years. Nearly half of the patients practiced in the informal sector 47.9%, were uneducated in 38.1% of cases and lived with a partner in 73.1% of cases. The majority of patients in this series 75.1% performed at least 4 ANCs. Patients were followed by prenatal visits in 61% of cases by midwives and in 8.6% of cases had an inter-reproductive space of less than 18 months. This study patients were evacuated in 46.4% of cases. Acute fetal distress was the first indication of first iterative caesarean section with 20.3% of cases. Emergency caesarean sections accounted for 84.4% of the cases in this series. Authors found maternal death 0.3% and 6.7% perinatal mortality. Conclusions: The iterative caesarean section is a caesarean section likely to cause difficulties and complications per- operative. Although in constant improvement the prognosis of the mother-child couple still remains a problem in this context, prenatal monitoring should be the prerogative of obstetrician gynecologists.